Relationship Marketing Strategies in the Dimension Stone Sector - Guidi, Antonio Carlos; Pizzinatto, Nadia Kassouf (Archives of Business Research, 2023)
This research investigated the most effective relationship marketing (RM) strategies in the US dimension stone sector (DSS) market: the overall objective of this research was to investigate which RM strategies are the most suitable, in order to improve the international dimension stone market. Methodologically, qualitative research was implemented, focusing on grounded theory. We interviewed three Brazilian distributors established in the USA, and fifteen national distributors who export dimension stones. Data analysis indicated that the RM strategies which best suited the sector in the American market were: prospecting for new customers, international partnerships, and customer loyalty. Thus, we identified the profile which best suited American consumer potential.